Team versus individual sport participation as a modifying factor in the development of post-concussion syndrome after first concussion: A pilot study. Issue 3 (3rd July 2019) - Jeckell, Aaron S.; Brett, Benjamin L.; Totten, Douglas J.; Solomon, Gary S.
ABSTRACT: Identification of modifying factors that influence the development of post-concussion syndrome (PCS) following sport-related concussion (SRC) has drawn considerable interest. In this pilot study, we investigate the effect of team vs. individual sport participation on the development of PCS in a sample of 136 high school and college student-athletes. Controlling for several confounding variables, we employed a binary logistic regression and chi-squared test. Results of this pilot study indicate that participation in team versus individual sport is not a significant factor in the development of PCS. The identification of other forms of protective mechanisms is discussed.